Kei Hiruta: Hannah Arendt and Isaiah Berlin: Freedom, Politics and Humanity, Princeton University Press 2021. : Hannah Arendt and Isaiah Berlin: Freedom, Politics and Humanity, by Kei Hiruta. - García-Arnaldos, Mª Dolores (HannahArendt.net, 2022)
The first thing to notice about Kei Hiruta’s monograph is that it is not a partisan book. The second is that it is one of those works that, while including the historical itinerary, also covers the philosophical debate that runs through it. Kei Hiruta’s research is thus, located at the intersection of political philosophy and intellectual history. The present monograph is the outcome of his project entitled “Berlin’s Bête Noire: Hannah Arendt and Isaiah Berlin on Freedom, Politics, and Humanity” which chronicles the intellectual, political, and personal conflict between Arendt and Berlin. Hiruta has also edited the book Arendt on Freedom, Liberation, and Revolution (Palgrave Macmillan, 2019). Here, the author delves into the idea of freedom and totalitarianism as points of disagreement and agreement between two giants of twentieth-century thought. He thus elaborates a concise and essential document of political theory.